Takhrij and Syarah Hadith of Agrotechnology The Virtue of Farming - Tubagus Adiwijaya; Suryaman Birnadi; Wahyudin Darmalaksana (Gunung Djati Conference Series, 2021)
The purpose of this study is to discuss the hadith of the Prophet Muhammad. about farming. The research method used in this research is a qualitative method through the approach of agrotechnology takhrij and sharah hadith. Results and discussion of this research is a farming activity that was encouraged by the Prophet Muhammad, and is still developing in modern times. The conclusion of this study is the farming activities suggested by the Prophet Muhammad. and also has many other benefits.